Integration of Mui Fatwa Commission's Ijtihad Method in Islamic Religious Learning based on Problem Based Learning - Syahrullah Syahrullah; Deden Edi; Fajar Harguna Endra Putra; Hardjadinata Hardjadinata (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Most of the students of class X MA Yapis North Jakarta, around 60%, the learning achievement is in the range of 40% of the total number of students as many as 64 in 2 classes have difficulty in understanding the material of fiqh, especially in linking the concept of Islamic law with contemporary life issues. Learning that tends to be rote and less applicable is one of the main factors that hinders students' understanding. To overcome this problem, this study aims to integrate the ijtihad method used by the Fatwa Commission of the Indonesian Ulema Council (MUI) into Islamic Religious Education learning based on Problem Based Learning (PBL). The contextual and systematic ijtihad method of the MUI Fatwa Commission is considered relevant to provide an understanding of Islamic law that is actual and responsive to social dynamics. This study uses a descriptive qualitative approach with a case study method. Data collection was carried out through classroom observations, interviews with teachers and students, and learning documentation. Initial results show that the integration of the ijtihad method in the PBL model is able to increase student participation, build critical thinking skills, and make fiqh material closer to the reality they face. Thus, this approach provides an effective alternative in improving the quality of fiqh learning in madrasas. The results of the research findings showed a significant increase in the percentage of students achieving scores above the KKM to 86%. This increase not only reflects the success of students in understanding the material cognitively, but also shows an increase in critical thinking, communication, and cooperation skills in the context of fiqh learning.